2021
DOI: 10.1038/s41467-021-25882-z
|View full text |Cite
|
Sign up to set email alerts
|

Peering into lunar permanently shadowed regions with deep learning

Abstract: The lunar permanently shadowed regions (PSRs) are expected to host large quantities of water-ice, which are key for sustainable exploration of the Moon and beyond. In the near future, NASA and other entities plan to send rovers and humans to characterize water-ice within PSRs. However, there exists only limited information about the small-scale geomorphology and distribution of ice within PSRs because the orbital imagery captured to date lacks sufficient resolution and/or signal. In this paper, we develop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…The mapped umbral craters have diameters between ∼5 and ∼384 m. In the majority of PSRs the crater size frequency distribution (CSFD, available in the supplementary information) bends/rolls over at crater diameters of ∼9–∼11 m, similar to the observations made by Bickel et al. (2021) in other south polar PSRs. This likely is an artifact of the resolution and denoising performance of HORUS, not caused by a physical process.…”
Section: Cryogeomorphology Of the Artemis Exploration Zone Shadowed R...supporting
confidence: 83%
See 2 more Smart Citations
“…The mapped umbral craters have diameters between ∼5 and ∼384 m. In the majority of PSRs the crater size frequency distribution (CSFD, available in the supplementary information) bends/rolls over at crater diameters of ∼9–∼11 m, similar to the observations made by Bickel et al. (2021) in other south polar PSRs. This likely is an artifact of the resolution and denoising performance of HORUS, not caused by a physical process.…”
Section: Cryogeomorphology Of the Artemis Exploration Zone Shadowed R...supporting
confidence: 83%
“…The geologic origin of two of those features (O01b, N01a, ∼175-∼450 m long) remains unclear, although the features appear to follow the local contour lines, that is, might be caused by/related to (slow) mass wasting (e.g., creep processes). We note that the PSRs and surrounding TSRs (transiently shadowed regions) in the studied section of the Artemis exploration zone appear to host fewer lobate features than were identified in other south polar regions (Bickel et al, 2021)-an initial observation that requires further confirmation. The lobate feature in PSR M01e appears to be the surface expression of a potential lobate scarp recently identified by Bernhardt et al (2022) in the sunlit area around PSR M01e.…”
Section: Crater Boulder and Lobate Feature Populationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Machine learning technology is being used for tasks other than just crater detection. It has been shown that surface ice can be detected by removing noise in high-resolution images in the Permanently Shadowed Regions (PSR), further revealing previously undetectable geological features of craters [74,75]. Figure 4 shows the topographic map of the lunar south pole, including the PSRs (black polygons).…”
Section: The Direction Of Research Related To the Moonmentioning
confidence: 99%
“…Figure 4 shows the topographic map of the lunar south pole, including the PSRs (black polygons). The blue polygons are the study points [74]. While researching the Moon, the following problems were identified.…”
Section: The Direction Of Research Related To the Moonmentioning
confidence: 99%